Valuing rail transit: Comparing capital and operating costs to consumer benefits - Erick Guerra (University of California, Institute of Urban and Regional Development (IURD), 2010)
A certain acrimony pervades the longstanding debate over the costs and benefits of public rail transportation in the United States. Some seem opposed to all rail transit all the time, while others support any and every rail project, despite sometimes high costs and low ridership. With much of the debate focused on pricing automobile externalities, transportation choice, and the rail's external benefits, surprisingly few studies assess which rail transit systems create net positive social welfare. If consumer benefits alone do not justify the high cost of a transit investment, what would the external value of a passenger trip have to be to do so? Combining fare, ridership, operating, and capital cost data for 24 transit agencies' heavy and/or light rail systems, this paper makes back-of-the-envelope estimates of how transit systems' rider benefits compare to operating deficits. Urban rail systems may not be optimal from a transportation systems or economic cost-benefit perspective, but they clearly create value for consumers and society. Given a low, but commonly applied, elasticity of -0.3 and a linear demand curve, two transit systems create net social welfare gains based solely on consumer surplus. At least ten others likely provide net benefits when accounting for economic externalities. At an elasticity of -0.6, no system provides net social welfare gains without accounting for externalities. At least five systems are unlikely to provide net economic benefits, even given generous assumptions about external and rider benefits.
Keywords: 330